Legal Protection for Creditors Who Recipient of Motor Vehicle Fiduciaries After Constitutional Court Decision Number 18/PUU-XVII/2019 & Number 2/PUU-XIX/2021 (Study at BRI Finance Malang Branch) - Ahmad Shoifi; Djumikasih, Djumikasih; Laila, Fathul (CV. AFDIFAL MAJU BERKAH, 2024)
Fiduciary is a material guarantee which is a development of other material guarantees, namely Pawning. This development is a living need in society because pawning collateral which requires control of the pledged collateral object by the creditor is felt to be less supportive of business because the debtor cannot benefit from the collateral object so material collateral is needed which is more beneficial for the debtor but also the creditor's interests can still be protected. Execution of fiduciary guarantees can be carried out in accordance with article 29 UUJF, namely if the debtor or fiduciary person breaks his promise, the execution of the object that is the object of fiduciary guarantee point 1 above is the priority given by the material guarantee institution which is referred to as Parate execution, which is regulated in Article 15 paragraph (3) of the Fiduciary Guarantee Law (hereinafter abbreviated to